1996
DOI: 10.1007/s002689900046
|View full text |Cite
|
Sign up to set email alerts
|

Total Pancreatectomy for Cancer of the Pancreas: Is It Appropriate?

Abstract: During the late 1960s total pancreatectomy was advocated on theoretic grounds as an operation superior to subtotal (Whipple) resection in patients with pancreatic cancer. There are, however, no prospective randomized studies and only few institutional comparisons between the two operations. The aim of the present paper was to report the clinical outcome of total and subtotal pancreatectomy, respectively, in a consecutive series of patients with exocrine pancreatic cancer. The short- and long-term results of 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 24 publications
(25 reference statements)
3
75
0
4
Order By: Relevance
“…This apancreatic diabetes can lead to severe episodes of hypoglycemia that can be very difficult to manage and can even lead to death. 12,46 In our series, none of the patients died from postresection diabetes during follow-up. In seven of the eight patients, diabetes was controlled with insulin treatment.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…This apancreatic diabetes can lead to severe episodes of hypoglycemia that can be very difficult to manage and can even lead to death. 12,46 In our series, none of the patients died from postresection diabetes during follow-up. In seven of the eight patients, diabetes was controlled with insulin treatment.…”
mentioning
confidence: 93%
“…This is a procedure that might be considered because it can improve glucose tolerance after resection, and it might prevent the postoperative diabetes seen after total pancreatectomy. 46,47 Patients with severe and persistent pancreatic leakage can receive completion pancreatectomy without additional morbidity and mortality. Completion pancreatectomy for leakage is a very aggressive treatment and is not the first step in treatment of pancreatic leakage.…”
mentioning
confidence: 99%
“…Most of these series consist of procedures performed in an older era with higher mortality and morbidity after pancreatic resections compared with today. Both Karpoff et al [21] and Ihse et al [22] reported worse survival after TP than after a more limited pancreatectomy, whereas Sarr et al [20] did not note any survival differences. Only Ihse et al [22] accounted for differences in stage and lymph node status between groups of patients that underwent TP and subtotal pancreatectomy.…”
Section: Total Pancreatectomy (Tp)mentioning
confidence: 96%
“…Both Karpoff et al [21] and Ihse et al [22] reported worse survival after TP than after a more limited pancreatectomy, whereas Sarr et al [20] did not note any survival differences. Only Ihse et al [22] accounted for differences in stage and lymph node status between groups of patients that underwent TP and subtotal pancreatectomy. They demonstrated an independent survival benefit for subtotal pancreatectomy versus TP (relative risk, 0.63; 95% confidence interval, 0.40 -0.99) with less postoperative mortality (3% versus 27%).…”
Section: Total Pancreatectomy (Tp)mentioning
confidence: 96%
“…Radical resection is not indicated if extrapancreatic nerve plexus around the superior mesenteric or celiac artery is invaded since dissection around these mesenteric vessels to harvest distant lymph nodes disrupts the plexuses resulting in severe diarrhoea postoperatively [9,10]. Also, most studies reveal no survival benefi t and increased morbidity and mortality with total pancreatectomy over pancreaticoduodenectomy and distal pancreatectomy [11,12]. However, in rare situations including a soft pancreas with risk of a leak from pancreatoenterostomy, or if positive margins on sequential frozen sections are obtained while resection is carried out into the pancreatic tail, or if there are papillomatous changes or dysplasia throughout the pancreatic duct, or if a family history of multicentric disease exists total pancreatectomy should be considered [13].…”
Section: Introductionmentioning
confidence: 99%